2012
DOI: 10.1016/j.burns.2011.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical studies of the High-Intensity Narrow-Spectrum light Environmental Decontamination System (HINS-light EDS), for continuous disinfection in the burn unit inpatient and outpatient settings

Abstract: Infections are the leading cause of morbidity and mortality in burn patients and prevention of contamination from exogenous sources including the hospital environment is becoming increasingly emphasised. The High-Intensity Narrow-Spectrum light Environmental Decontamination System (HINS-light EDS) is bactericidal yet safe for humans, allowing continuous disinfection of the environment surrounding burn patients. Environmental samples were collected from inpatient isolation rooms and the outpatient clinic in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 26 publications
(35 reference statements)
1
74
0
Order By: Relevance
“…The results presented in this paper provide proof-of-concept validation that synergistic sporicidal activity can be achieved using spore suspensions and high irradiance levels, however it would be of great interest in future studies to replicate the results with contaminated surfaces representative of what would be expected within the clinical environment, and lower 405 nm light irradiance levels such as those used for environmental decontamination applications [13,14]. A limiting factor of 405 nm light over other technologies such as UV-light, hydrogen peroxide vapour or ozone, is the lower sporicidal activity, however the ability to enhance this activity through its combined use with disinfectants -which would already be in routine use within the hospital environment -coupled with the ability to apply this technology safely in the presence of patients and staff [17][18][19] gives this technology attractive features for provision of continuous environmental decontamination against C. difficile.…”
Section: * Represent Significant Bacterial Inactivation (P≤005) Eacmentioning
confidence: 98%
See 2 more Smart Citations
“…The results presented in this paper provide proof-of-concept validation that synergistic sporicidal activity can be achieved using spore suspensions and high irradiance levels, however it would be of great interest in future studies to replicate the results with contaminated surfaces representative of what would be expected within the clinical environment, and lower 405 nm light irradiance levels such as those used for environmental decontamination applications [13,14]. A limiting factor of 405 nm light over other technologies such as UV-light, hydrogen peroxide vapour or ozone, is the lower sporicidal activity, however the ability to enhance this activity through its combined use with disinfectants -which would already be in routine use within the hospital environment -coupled with the ability to apply this technology safely in the presence of patients and staff [17][18][19] gives this technology attractive features for provision of continuous environmental decontamination against C. difficile.…”
Section: * Represent Significant Bacterial Inactivation (P≤005) Eacmentioning
confidence: 98%
“…A recent technology that has been proposed for environmental decontamination applications is the use of 405 nm violet-blue light [13][14][15][16]. Recent studies carried out in hospital isolation rooms have demonstrated the use of this technology for continuous decontamination of occupied environments, with reductions in the levels of bacterial contaminants by up to 80%, over and above that achieved with standard cleaning and infection control procedures alone [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not yet commercially available, this user-friendly, ceiling-mounted light source has been evaluated within clinical environments with successful results [57][58][59].…”
Section: Nm Violet-blue Lightmentioning
confidence: 99%
“…Further confirmation of the effectiveness of the system was obtained by switching off the EDS and observing that bacterial contamination levels increased and returned to around pre-treatment levels when operation of the system ceased. In addition to its use for disinfection of occupied isolation rooms, a study by Bache et al [58] demonstrated the efficacy of the system for decontamination of a Burns outpatient clinic, with a 61% efficacy achieved. Results have also demonstrated its efficacy for significantly reducing the environmental microbial contamination of non-patient environments including a nurses changing area [60].…”
Section: Nm Violet-blue Lightmentioning
confidence: 99%